2007
DOI: 10.1007/s11199-007-9284-3
|View full text |Cite
|
Sign up to set email alerts
|

Do Third-Person Perceptions of Media Influence Contribute to Pluralistic Ignorance on the Norm of Ideal Female Thinness?

Abstract: This study investigated the pluralistic ignorance on the norm of ideal female thinness and also the presumed influence of thin idealized media images as the cause of the misperception. A survey of 111 female and 109 male US undergraduate students revealed that both women and men overestimated the thinness of body type preferred by others. In addition, men reported that others would be more affected by the media than self while women considered themselves to be as vulnerable as others. Subsequent regression ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
10
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 51 publications
5
10
0
3
Order By: Relevance
“…Those who expressed more concern about their appearance and placed themselves in a passive role were more concerned about their weight than girls whose dating scripts were more activity-focused and less gender-typed. Both women and men also overestimated the thinness of the female body type preferred by others of the same-gender and the opposite-gender (Park et al 2007), demonstrating that the norm of female thinness was alive and well.…”
Section: Cultural Scriptsmentioning
confidence: 93%
“…Those who expressed more concern about their appearance and placed themselves in a passive role were more concerned about their weight than girls whose dating scripts were more activity-focused and less gender-typed. Both women and men also overestimated the thinness of the female body type preferred by others of the same-gender and the opposite-gender (Park et al 2007), demonstrating that the norm of female thinness was alive and well.…”
Section: Cultural Scriptsmentioning
confidence: 93%
“…For example, for college women, male peers form a more dissimilar and socially distant comparison group than female peers. College women tended to report a greater third-person perception in relation to idealized body image when the comparison group was male peers than when the comparison group was female peers (Chia 2007 for college women in Singapore; Goodman and Walsh-Childers 2004;Park et al 2007 for college women in the United States). College women were also tempted to accommodate their male friends (Goodman and Walsh-Childers 2004).…”
Section: Social Distance and Perceived Media Effectsmentioning
confidence: 94%
“…In the context of media's idealized body images, college men are as capable as college women of realizing the socially undesirable outcomes of being affected by the images. When being asked to estimate the effects of idealized female body images in the media, college men in the United States reported that the media effect on peers was greater than the media effect on the self (Park et al 2007). In this study, we extend the examination to Chinese college men in Singapore.…”
Section: Third-person Perceptions About Body Imagementioning
confidence: 96%
“…A study by Park and Yun (2007) with academics showed that the media has a strong influence on this situation, and women overestimate the stereotype because of pluralistic ignorance.…”
Section: People's Attitudementioning
confidence: 99%